ANALYSIS OF FINANCIAL PERFORMANCE WITH USING ECONOMIC VALUE ADDED: A STUDY ON INDOFOOD CBP SUKSES MAKMUR - Yanti; Isyanto, Puji; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to determine the financial performance. Indofood CBP Sukses Makmur Tbk in 2015 until 2018, based on the method of EVA. The data used in this study a financial statement data from 2015 to 2018 year. Data analysis method used is descriptive statistical analysis methods. From the data analysis berdasarkankan EVA method shows good performance for over 4 years of research EVA company shows a negative value ((EVA <0). The results showed that PT. Indofood CBP Sukses Makmur Tbk.’Re unable to create added value is positive. It could occur because of high cost of capital is not followed by increasing the value of Net operating profit After Taxes lower earnings to increase the amount of debt in the company. EVA obtained is always negative can be influenced by the amount of profit that is less than the amount of debt is high enough, it can lead to lack of interest of the shareholders to invest in the Company. Despite the negative EVA value but the company still has a positive profit so that the company is still viable and very still in demand by investors.